2017
DOI: 10.1002/phar.1902
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Management of Patients with Heroin versus Nonheroin Opioid Overdoses: Experience at an Academic Medical Center

Abstract: This study indicates that the incidence of heroin overdoses has significantly increased over the last several years, and the rates of HCV infection 4-fold since the start of the study period. Patients admitted for nonheroin opioid overdose were more likely to be admitted to the hospital and intensive care unit compared with those admitted for heroin overdose. The rise in overdose events only further illustrates a gap in our understanding of the cycle of addiction, drug abuse, and overdose events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…With the increased morbidity associated with pain-related conditions such as cancer, morphine abuse has escalated worldwide and has become a serious global problem [3]. It has been reported that almost half of the accidental drug deaths can be attributable to morphine or heroin overdose [4]. Chronic exposure to morphine leads to increased complications such as addiction, tolerance, cognitive impairment, withdrawal, and severely compromised immune system with an increased risk of opportunistic infections [512].…”
Section: Introductionmentioning
confidence: 99%
“…With the increased morbidity associated with pain-related conditions such as cancer, morphine abuse has escalated worldwide and has become a serious global problem [3]. It has been reported that almost half of the accidental drug deaths can be attributable to morphine or heroin overdose [4]. Chronic exposure to morphine leads to increased complications such as addiction, tolerance, cognitive impairment, withdrawal, and severely compromised immune system with an increased risk of opportunistic infections [512].…”
Section: Introductionmentioning
confidence: 99%
“…Many patients who present with opiate overdose tend to have a repeated event after an ED visit and may experience multiple overdose events before a fatal outcome. 64 One of the challenges of providing appropriate care and counseling for patients with opioid use disorder in the ED is time. ED clinicians are often working in a chaotic environment and juggling multiple tasks, making it difficult to find time to counsel patients and provide them with appropriate long‐term follow‐up.…”
Section: Discussionmentioning
confidence: 99%
“…ED clinicians are on the front line of caring for patients with opioid dependence, from treatment of withdrawal symptoms to signs of opioid overdose, psychiatric or medical emergencies, and trauma. Many patients who present with opiate overdose tend to have a repeated event after an ED visit and may experience multiple overdose events before a fatal outcome 64 . One of the challenges of providing appropriate care and counseling for patients with opioid use disorder in the ED is time.…”
Section: Discussionmentioning
confidence: 99%
“…From July 2016 to September 2017, visits for opioid-related overdoses rose 30% in the United States ii . Recent data show that many opioid overdose victims will have a repeat overdose event after ED admittance without outpatient treatment [2]. Current treatment referral procedures from the ED are insufficient, with only 37% of ED referrals leading to treatment engagement at 30 days post the initial encounter with a simple referral to outpatient treatment [3].…”
Section: The Opioid Epidemicmentioning
confidence: 99%